CONVERGENT AND DIVERGENT THOUGHT PROCESSES IN SCIENTIFIC THINKING - Toshpulatov Ibrahim Ikromjonovich; Mingboyeva Gulchehra Muhammadjonovna; Ikromjonova Diyora Ibroxim qizi; Ikromjonova Zilola Ibrohim qizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In this article, the author has analyzed the practical importance of the thinking process used to create creative ideas by studying many possible solutions in convergent and divergent thinking and creativity in the effective organization of educational work for young people today. In addition, he emphasized that teachers should have sufficient knowledge, skills and qualifications in pedagogy, psychology, and pedagogical skills in order to effectively organize pedagogical activities. During the article, the effective organization of activities by early identification of children with high or low intelligence and high or low creativity was also widely covered.